ANALISIS INTERVENSI SENSORY STIMULATION (SUARA KELUARGA) TERHADAP TINGKAT KESADARAN PASIEN DENGAN PENURUNAN KESADARAN (GCS RENDAH) - Syahla Indira Dewi (Jurnal Medika Hutama, 2026)
Abstract Impaired consciousness is a serious condition that often occurs in patients with traumatic brain injury, stroke and other critical conditions, and is associated with high morbidity and mortality rates in the Intensive Care Unit (ICU). Patients with low Glasgow Coma Scale (GCS) scores require effective interventions to increase consciousness. One of the non-pharmacological approaches that is developing is sensory stimulation, especially auditory stimulation using family sounds. The aim of this study was to analyze the effectiveness of sensory stimulation intervention (family voice) on the level of awareness of patients with low GCS. The method used is Systematic Literature Review (SLR) with an Evidence-Based Practice (EBP) approach following PRISMA guidelines. A literature search was conducted on several indexed databases and 10 articles were obtained that met the inclusion criteria for narrative analysis. The result is that family sound-based sensory stimulation is effective in increasing GCS scores, accelerating recovery of consciousness, and increasing the patient's physiological stability. In conclusion, family voice stimulation is an effective intervention and can be implemented as part of family-based care in the ICU.